Analisis Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan - Ginting Munthe, S.E., M.Si, Rikawati; br Sitepu, Conie Nopinda; Br Sitepu, Agnes Arta Femi (JURNAL REGIONOMIC, 2025)
This study aims to measure the effect of service quality and product quality on customer satisfaction carried out at the Sofi Kebaya tailor. The independent variables are service quality and product quality and the dependent variable is customer satisfaction. This research method is quantitative descriptive analysis and measures the influence between variables using multiple regression analysis. Service quality and product quality simultaneously affect customer satisfaction by 19.2%. Partial Test states that customer satisfaction is not affected by service quality but product quality affects customer satisfaction.